PEMBUATAN PROTOTYPE SMS GATEWAY NOTIFIKASI ALARM BASE STATION PADA DIVISI TELKOM FLEXI KANTOR PERWAKILAN YOGYAKARTA - , Pieldra Sinaga ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Base Station is one of telecommunication components that takes care signal transmission and interconnection with other telecommunication components. In general, base stations spread out in distant area in order to facilitate whole customers to communicate. Disturbance occurred at the base station significantly influence the communication process, ranging from unable to make calls, drop calls or unclear sound. The disturbances are such as power failure, damaged modules and transmission problems. Because of the dispersed location of base stations, the officers in charge to manage are also deployed in each area. Thus, when a disturbance happens in the base station, the existing process is manual notification from the picket officer either by telephony or SMS. SMS Gateway is a gateway for information dissemination by using SMS. By utilizing SMS Gateway, the information can be directly sent to the related parties. Disturbances that occur at the base station are stored in the logs in real time on central server. These logs will then be processed to obtain information associated with the base station. Next step, the information will be sent to the related parties using SMS Gateway. With this rapid process of delivery, prevention and solving process are expected to increase the base stationâs stability. In this study, the author has conducted an analysis to the subject and the results are intended to contribute to the organization. In addition, the author also concluded that SMS Gateway can be applied by utilizing information from log data processing and Gammu service. From the testing, SMS Gateway can function accordance with the user requirements.